The Role of System Engagement in Tax Compliance Burden: The Moderating Role of Tax Education - Milamo, Rufina Justine; Magobe, Mato James (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
This study investigates the impact of taxpayers’ engagement with the e-filing tax system on the tax compliance burden, while also examining how tax education moderates this relationship. Drawing on survey data from 705 medium and large taxpayers in Tanzania, the study finds that both the use of the e-filing system and tax education significantly reduce the compliance burden. Moreover, tax education enhances the positive effects of e-filing system usage by empowering taxpayers with the necessary skills, further easing their compliance efforts. This research makes a valuable academic contribution by showing that sustained use of the e-filing system, combined with tax education, can reduce compliance burdens and improve taxpayer competence. Practically, the findings underscore the need for tax authorities to enhance the usability and service quality of e-filing systems and emphasize the importance of investing in tax education. These insights are essential for policymakers and tax authorities aiming to optimize the effectiveness of e-filing within a mandatory adoption context and to promote tax compliance through targeted educational initiatives.